Improving student achievement by using interactive Learning model of ips lesson in natural appearance At the first grade students of sd negeri 43 siguntur in Academic year 2015/2016 - Yuspi Yuspi (Jurnal Ilmiah Pendidikan Scholastic, 2017)
The purpose of this study is to prove that the use of the environment around the school to enhance students' understanding of the events of Islamic religious education in students of Class I V In S D Affairs No. 43 Siguntur Young. This study uses a class action approach. The study population was taken of all students in grade IV , the data collection techniques used artificial teacher learning achievement test. Actions performed a total of two cycles. Data analysis techniques used analysis of the percentage of change in the results of the evaluation study before and after tutoring services with peer tutors. Thus there is an increasing mastery learning students from the first cycle to the second cycle. Based on the above, it can be made a conclusion as follows: " Improve Student Achievement 43 Siguntur Young Elementary School Using Interactive Learning Model Lesson In Nature IPS About Appearance Semester 1 Academic Year 2015/2016 "In the pre-study enrollment who did not complete the following study is very high. After the implementation of the learning improvement in Cycle 1 appears once improving student learning outcomes at 70%, 16 students have been completed and 7 students are still unresolved. In cycle 2 had peninkatan significantly by 88%. Based on the description and discussion of the above results begin to cycle 1 to cycle 2 regarding the use of interactive learning model, can the authors conclude that: 1) By using interactive learning, was able to improve student achievement Elementary School fourth grade No. 43 Siguntur Young on the material of natural appearance. 2) Through interactive learning, students can be more active in learning activities, particularly in social studies